1999
DOI: 10.1007/s004020050348
|View full text |Cite
|
Sign up to set email alerts
|

Effects of glucocorticoids on bone mineral density in rheumatoid arthritis patients

Abstract: We carried out a comparative study in 78 post-menopausal women with rheumatoid arthritis (RA). Forty-four women with a mean disease duration of 17.5 years had been treated with low-dose glucocorticoid (prednisone at < 5 mg/day) for at least 12 months. They were studied for an average period of 3 years and 8 months. The remaining 34 women had been treated only with nonsteroidal anti-rheumatic drugs (NSAIDs) and served as the control group. Bone mineral density (BMD) in the lumbar spine (L2-4) and femoral neck w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2002
2002
2008
2008

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Thirty-five studies were identified by electronic or manual search, and 13 were selected for full text review based on title/abstract. 7–13,2226 However, 6 of the 11 were excluded; 4 were nonrandomized studies, 10,2224 and the other 2 had no BMD data. 25,26 Thus, 7 studies met the inclusion criteria.…”
Section: Resultsmentioning
confidence: 99%
“…Thirty-five studies were identified by electronic or manual search, and 13 were selected for full text review based on title/abstract. 7–13,2226 However, 6 of the 11 were excluded; 4 were nonrandomized studies, 10,2224 and the other 2 had no BMD data. 25,26 Thus, 7 studies met the inclusion criteria.…”
Section: Resultsmentioning
confidence: 99%
“…This study (referred to as the General Practice Research Database (GPRD) study) was conducted in a general practice setting in the UK [75][76][77][78][79]. There were a further 29 smaller studies which have also investigated fracture [16,22,30,38,41,52,57,58,68,74,[80][81][82][83][84][85][86][87][88][89][90][91][92][93][94][95][96][97][98]. Six studies were excluded from the analysis due to insufficient information for OR calculation [41,52,80,83,90,96].…”
Section: Results Of Reviewmentioning
confidence: 99%
“…Studies of patients using daily doses on average of 7.5 mg prednisolone or lower at the time of BMD measurement found conflicting results. Several studies found no substantive reductions in BMD at lower doses [15,16,18,26,28,37,39,[54][55][56][57]102,103], in contrast to others [29,30,36,43,47,68,98,105]. Interpretation of these results is complicated because the daily doses used prior to the BMD measurement were frequently unknown and not taken into account.…”
Section: Relationship To Cs Dosementioning
confidence: 96%